The Impact Of Sharenting Practices In Whatsapp Story On The Formation Of Self-Identification Of Early Childhood In Sribit Village, Wonolelo - Mei Setianingsih; Ahmad Khoiri; Vava Imam Agus Vaisal (FKIP UNSULTRA, 2026)
This study examines the impact of sharenting practices on WhatsApp Story on the formation of early childhood identity in Dusun Sribit, Wonolelo Village, Wonosobo. The increasing use of digital media in parenting has transformed family communication patterns, where parents frequently share children’s daily activities online without fully considering their psychological and digital privacy implications. The objective of this research is to explore the forms of sharenting practices, parental motivations, and their effects on children’s self-awareness, self-concept, and social identity development. This study uses a qualitative descriptive method with a field research approach. Data were collected through semi-structured interviews, observation, and documentation involving ten parents with early childhood children aged 3–6 years who actively use WhatsApp Story. The results show that sharenting practices include sharing children’s achievements, daily activities, independence development, and humorous moments, with an average frequency of 2–4 uploads per week. Parental motivation is dominated by the desire to share happiness, document children’s growth, train children’s confidence in front of the camera, and fill leisure time. The findings indicate that sharenting has both positive and negative impacts on children’s identity formation. Positively, it enhances self-confidence and social recognition. However, it also risks creating dependence on external validation, shaping self-image based on social feedback, and influencing emotional stability. In conclusion, sharenting practices on WhatsApp Story play a significant role in shaping early childhood identity in a dual manner, contributing to both psychological development and potential risks in digital identity formation.